Pengaruh Kecepatan Pengadukan Pada Pembuatan Bioetanol Dari Pelepah Sawit Menggunakan Saccharomyces Cerevisiae - Meilano Ashari Akbar; Adrianto Ahmad; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Indonesia is one of the largest oil producer in the world. Palm frond is a type of plant lignocellulose comprising lignin, cellulose and hemicellulose. Where the presence of cellulose, the palm fronds can be used as raw material in the manufacture of bioethanol by converting cellulose into glucose. Bioethanol production from palm fronds can be done through a process of fermentation. The microorganisms used in this study was Saccharomyces cerevisiae. The purpose of this study was to determine the effect of stirring speed in the fermentation process to produce bioethanol produced to determine the best time and fermentation to ethanol conversion of palm fronds. Steps being taken in this study include delignification, purification powder palm fronds, hydrolysis and fermentation. In the fermentation process variation stirring speed of 100 rpm, 150 rpm, 200 rpm, and 250 rpm. The results showed that the hydrolysis of cellulose by acid produced initial sugar concentration to a maximum of 82,41 g/L. The best stirring speed in this research is 250 rpm and the best fermentation time is 96 hours with ethanol levels obtained at 3% or 23,67 g/L.Keywords : bioethanol, fermentation, hydrolysis, saccharomyces cerevisiae, stirring